2021
DOI: 10.18038/estubtda.984915
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical and Physical Properties of Graphene With Epoxy Matrix

Abstract: Composite materials have become a highly preferred technology nowadays in the industry with their advantages such as superior mechanical performance and weight loss for aerospace applications, especially due to the combination of different components and the formation of new products. In addition, with nanocomposites, this technology skips a step further and allows more effective products to be produced. Nanocomposites are produced using carbon allotropes such as graphene and carbon nanotubes, which have the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…According to the experience gained in previous studies, 36,37 it has been observed that working at low concentrations by weight both provides the desired output and is successful in creating a homogeneous mixture in thermoset resins if the relevant percolation threshold is expected to be low which is provided for the in this study used epoxy system 38,39 . Therefore, in this study, 0, 0.1, 0.25, 0.5 and 1 wt% of fillers were mixed into the epoxy resin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the experience gained in previous studies, 36,37 it has been observed that working at low concentrations by weight both provides the desired output and is successful in creating a homogeneous mixture in thermoset resins if the relevant percolation threshold is expected to be low which is provided for the in this study used epoxy system 38,39 . Therefore, in this study, 0, 0.1, 0.25, 0.5 and 1 wt% of fillers were mixed into the epoxy resin.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental preliminary studies have been carried out to determine the suitability of this device, which is frequently used in industrial applications for experimental studies. As a result, mixing speed and cycle were optimized 36,37 . According to the process, nanomaterials were added to the resin sequentially according to data from DOE and mixed for 5 cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher concentrations nanoparticles may show agglomeration which forms stress concentrated regions that might cause earlier deformation of the matrix under loads. 6,27 However, an epoxy AgNW composite with 5 wt% AgNWs was produced to investigate effects of the AgNW amount on electromagnetic shielding properties of the composite. Moreover, a specific reinforcement ratio was chosen for preparing surface modified AgNW (m-AgNW) epoxy composites to improve the homogeneity of the composites while studying its effects on varying properties of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Composite manufacturing is significant for the aerospace industry because of preferred characteristics like enhanced strength/weight ratio, high durability limit under cyclic stresses and minimized corrosion issues of composites [1][2][3][4][5][6][7][8][9][10]. Composite parts are manufactured by several methods while the hand lay-up process is still used commonly.…”
Section: Introductionmentioning
confidence: 99%